The prospects of brewery waste application in biohydrogen production by photofermentation of Rhodobacter sphaeroides. (1st January 2021) - Hakobyan, Lilit; Gabrielyan, Lilit; Blbulyan, Syuzanna; Trchounian, Armen
Abstract: Selection of the source for biohydrogen (H2 ) production is essential, since it affects bacterial metabolism. Pure organic substrates give fast H2 generation with high yields, but they increase the production cost. Using industrial wastes as a source provides inexpensive energy generation with simultaneous waste utilization. H2 production by photofermentation of Rhodobacter sphaeroides is monitored during cultivation on brewery waste. Maximum specific growth rate is observed for 5–10% waste containing media. H2 production by cells, grown on waste, is detected at 48–96 h of growth; it is comparable or higher than that of control medium with expensive carbon and nitrogen sources. N, N′ -dicyclohexylcarbodiimide-sensitive ATPase activity of R. sphaeroides membrane vesicles from growth on waste containing media is 1.6–1.7-fold higher compared to control, correlating with enhanced H2 production. Growth medium containing optimal amount of wastes may be a successful alternative to expensive media for high H2 yield in R. sphaeroides during photofermentation. Highlights: Brewery wastes can serve an effective source for biomass and bio-hydrogen. R. sphaeroides growth rate was higher in the presence of diluted brewery waste. Diluted brewery waste enhanced (∼2.5 fold) H2 production by R. sphaeroides. The FO F1 -ATPase is involved in the increase of Н2 production.